Pengaruh Pajak, Kepemilikan Asing dan Tunneling Incentive terhadap Penerapan Transfer Pricing pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi di Bursa Efek Indonesia - Hasibuan, Renika; Purba, Rolita Christina (JURNAL MUTIARA AKUNTANSI, 2021)
The purpose of this study was to examine the effect of tax, foreign ownership and tunneling incentives on indications of transfer pricing in infrastructure, utility and transportation companies on the Indonesia stock exchange in 2014-2018. The population in this study are infrastructure, utility and transportation companies listed on the Indonesia Stock Exchange for the period in 2014-2018. The number of samples used was50 companies using purpose sampling method. The data processing program uses version 22 of the SPSS program. The analysis method used in this study is descriptive statistical test, classical assumption test, multiple linear regression, t statistical test, F statistical test, determination coefficient test (R2). and correlation test (R).The results showed that the tax variable had no effect on the indication of transfer pricing. The foreign ownership variable has no effect on the indication of transfer pricing. The tunneling incentive variable has an effect on the indication of transfer pricing. Based on the simultaneous test (F test), the variables of tax, foreign ownership, and tunneling incentives together have an effect on indications of transfer pricing in infrastructure, utility and transportation sector companies listed on the Indonesian stock exchange in 2014-2018.